Sophoridine Suppresses Herpes Simplex Virus Type 1 Infection by Blocking the Activation of Cellular PI3K/Akt and p38 MAPK Pathways - Tang, Qiong; Luan, Fei; Yuan, An; Sun, Jiayi; Rao, Zhili; Wang, Baojun; Liu, Yao; Zeng, Nan (Frontiers in Microbiology, 2022)
Herpes simplex virus type 1 (HSV-1) is ubiquitous and important human pathogens, which causes significant clinical diseases ranging from skin lesions to encephalitis, especially in immunocompromised and neonatal hosts. Currently, widely used nucleoside analogues including acyclovir and penciclovir have some limitations due to side effects and drug resistance. Here, we reported that sophoridine (SRI) could dramatically inhibit HSV-1 replication in vitro. SRI exhibit remarkable inhibitory effect on HSV-1 plaque formation and generation of progeny viruses, with the EC50 values of 0.112 and 0.064 mg/mL, respectively. Moreover, SRI significantly suppressed HSV-1 replication through inhibiting the expression of viral immediate early (ICP0 and ICP22), early (ICP8 and TK) and late (gB and gD) genes as well as the expression of viral protein ICP0, ICP8, gB and gD. In addition, we also suggested that SRI may inactivate virus particles directly and block some steps in HSV-1 life cycle after adsorption. Furthermore, SRI down-regulate the cellular PI3K/Akt pathway to further inhibit HSV-1 replication. Most importantly, SRI also markedly depressed HSV-1-induced p38 MAPK pathway activation. Collectively, the natural bioactive alkaloid SRI could be a promising therapeutic candidate to be developed into a novel anti-HSV-1 agent via modulation of cellular PI3K/Akt and p38 MAPK pathways.